First Principle Study of Phonon in BE2C - Gupta, Prakash Chanda (Shaheed Smriti Journal, 2021)
The phonon properties of Be2C of antifluorite structure was computed with ab initio Density Functional Theory calculations using the generalized gradient approximation (GGA). The structure is used as a UV resistive and hard material. The obtained phonon dispersion indicates antifluorite Be2C are dynamically stable and the obtained phonon DOS indicates high oscillations in the higher frequency ranges.